IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN SEKOLAH - Sumarsono, Raden Bambang; Benty, Djum Djum Noor; Wiyono, Bambang Budi; Maisyaroh, Maisyaroh; Supriyanto, Achmad (ABDIMAS PEDAGOGI, 2017)
Abstract: The purpose of this science, technology, and art (ipteks) implementation is that at the end of the activity, the Principal Principals in Blitar City can realize quality education through the implementation or implementation of School Based Management (SBM) in elementary school (SD). The target of community service activities is the Principal and Primary School Supervisor. The form of activities is community education, which is implemented through seminar and workshop techniques. The training methods used are varied, among others through lectures, questions and answers, discussions, brainstorming, task methods, exercises, sharing experiences, and consolidation. Based on the results of the evaluation, the outline of capacity building activities of school principals in realizing quality education through the implementation or implementation of school-based management in primary schools can be done well. The number of participants who attended 34 principals, from the number of participants who had more than 90% of the Principal is very active in following the seminar and workshop. All the attendees (100%) followed the activity thoroughly from start to finish. Judging from the results, more than 90% of principals and supervisors understand about the material presented by the resource person.Keywords: school quality, school based managementAbstrak: Tujuan kegiatan penerapan ilmu pengetahuan, teknologi, dan seni (ipteks) ini adalah agar pada akhir kegiatan, para Kepala Sekolah Dasar di Kota Blitar mampu mewujudkan pendidikan bermutu melalui penerapan atau implementasi MBS di SD. Sasaran kegiatan pengabdian kepada masyarakat ini adalah Kepala Sekolah Dasar dan Pengawas TK/SD. Bentuk kegiatannya adalah pendidikan masyarakat, yang dilaksanakan melalui teknik seminar dan lokakarya. Metode pelatihan yang digunakan secara bervariasi, antara lain melalui ceramah, tanya jawab, diskusi, brainstorming, metode tugas, latihan, sharing experiences, dan pemantapan. Berdasarkan hasil evaluasi, secara garis besar kegiatan peningkatan kapasitas kepala sekolah dalam mewujudkan pendidikan bermutu melalui penerapan atau implementasi manajemen berbasis sekolah di SD dapat terlaksana dengan baik. Jumlah peserta yang hadir 34 orang Kepala Sekolah, dari jumlah peserta yang hadri lebih dari 90% Kepala Sekolah sangat aktif dalam mengikuti kegiatan seminar dan lokakarya ini. Seluruh peserta yang hadir (100%) mengikuti kegiatan secara tuntas dari awal sampai akhir. Ditinjau dari hasilnya, lebih dari 90% Kepala Sekolah dan Pengawas memahami tentang materi yang disampaikan oleh narasumber.Kata kunci: manajemen berbasis sekolah, mutu sekolah